The labor market regimes of Denmark and Norway – One Nordic model?. (April 2015) - Gooderham, Paul N; Navrbjerg, Steen E; Olsen, Karen Modesta; Steen, Christina Roe
The literature on the Danish and Norwegian labor market systems emphasizes the commonalities of the two systems. We challenge this perception by investigating how employers in multinational companies in Denmark and Norway communicate with employees on staffing changes. We argue that the development of 'flexicurity' in Denmark grants Danish employers considerably greater latitude in engaging in staffing changes than its Nordic counterpart, Norway. Institutional theory leads us to suppose that large firms located in the Danish setting will be less likely to engage in employer–employee communication on staffing plans than their Norwegian counterparts. In addition, we argue that in the Danish context indigenous firms will have a better insight into the normative and cognitive aspects to flexicurity than foreign-owned firms, meaning that they are more likely to engage in institutional entrepreneurialism than their foreign-owned counterparts. We supplement institutional theory with an actor perspective in order to take into account the role of labor unions. Our analysis is based on a survey of 203 firms in Norway and Denmark which are either indigenous multinational companies or the subsidiaries of foreign multinational companies. The differences we observe cause us to conclude that the notion of a common Nordic model is problematic.